2015
DOI: 10.1590/s1980-65742015000100008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined aerobic and resistance training in body composition of obese postmenopausal women

Abstract: The aim of this study was to investigate the effects of a 16-week program of combined aerobic and resistance training on the body composition of postmenopausal women who are obese. The participants were divided into two groups: training group (TG, n = 37) and non-trained control group (CG, n = 18). The trunk fat, fat mass, percentage of fat mass and fat-free mass were estimated using DXA. Three nonconsecutive 24-hour dietary recalls were conducted. The training protocol consisted of 50 minutes of resistance tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…This category consisted of eight studies [25][26][27][28][29][30][31][32] with results related to the cardiovascular benefits if regular exercise in menopausal women. Three studies [25][26][27] demonstrated that exercise in postmenopausal women results in the elevation of antioxidant system, measured by the enzymes superoxide dismutase and glutathione peroxidase.…”
Section: Physical Exercise As a Strategy For The Prevention Of Cardiomentioning
confidence: 99%
See 1 more Smart Citation
“…This category consisted of eight studies [25][26][27][28][29][30][31][32] with results related to the cardiovascular benefits if regular exercise in menopausal women. Three studies [25][26][27] demonstrated that exercise in postmenopausal women results in the elevation of antioxidant system, measured by the enzymes superoxide dismutase and glutathione peroxidase.…”
Section: Physical Exercise As a Strategy For The Prevention Of Cardiomentioning
confidence: 99%
“…It is noteworthy that the work of Casas et al was the only study in our sample which Regarding arterial compliance, studies [29][30][31] showed that exercise improves this factor, reducing cardiovascular risk and blood pressure. One study 32 showed that the presence of polymorphism for the -786T>C position of the endothelial nitric oxide synthesis gene does not affect the basal levels of nitric oxide; however, when physical exercise is performed, nitric oxide concentration is reduced for women, with this polymorphism found in both normotensive and hypertensive women. Polymorphism is directly associated with cardiovascular diseases such as acute myocardial infarction and coronary artery disease.…”
Section: Physical Exercise As a Strategy For The Prevention Of Cardiomentioning
confidence: 99%
“…Comprovados os efeitos positivos de oito semanas de treinamento combinado no perfil metabólico, Rossi et al 53 objetivaram verificar os efeitos de 16 semanas de treinamento combinado na composição corporal de mulheres na pós-menopausa. Assim como no estudo de oito semanas, o grupo treinamento diminuiu a gordura total e de tronco, e aumentou a massa corporal magra.…”
Section: Treinamento Combinadounclassified
“…Several studies from our group had showed the benefits of different kinds of training on the body composition and metabolic profile in postmenopausal women ( Diniz et al, 2016 ; Neves et al, 2017 ; Rossi et al, 2013 ; Rossi et al, 2015 ; Rossi et al, 2016 ). Diniz et al (2016) demonstrated that only 8 weeks of aerobic training prescribed by the critical velocity was sufficient in reduced total FM, percentage of fat and low-density lipoprotein cholesterol (LDL-c) in postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“… Diniz et al (2016) demonstrated that only 8 weeks of aerobic training prescribed by the critical velocity was sufficient in reduced total FM, percentage of fat and low-density lipoprotein cholesterol (LDL-c) in postmenopausal women. Rossi et al (2013 , 2015) showed that resistance plus aerobic training in the same session (combined training, CT) was effective in improving fat-free mass (FFM) and decreased whole and trunk adiposity after short period and post-16 weeks of training.…”
Section: Introductionmentioning
confidence: 99%